2009
DOI: 10.1210/jc.2009-1327
|View full text |Cite
|
Sign up to set email alerts
|

Recessive Isolated Growth Hormone Deficiency and Mutations in the Ghrelin Receptor

Abstract: These data, which describe the first case of recessive partial isolated GH deficiency due to GHSR mutations and emphasize the physiological importance of the GHSR in somatic growth, are discussed in light of the dominantly expressed p.A204E mutation.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

3
58
0
5

Year Published

2011
2011
2021
2021

Publication Types

Select...
7
2

Relationship

0
9

Authors

Journals

citations
Cited by 86 publications
(67 citation statements)
references
References 30 publications
3
58
0
5
Order By: Relevance
“…In contrast to the Ala204Glu mutation which has been implicated in short stature with dominant transmission; recessive GHS-R mutations have also been reported (Pantel et al, 2009). The proband was born to unrelated parents of normal phenotype, presented with episodes of abdominal pain, vomiting, hypoglycemia, and ketosis and required glucose infusions.…”
Section: Ghs-r Mutations In Patientsmentioning
confidence: 97%
See 1 more Smart Citation
“…In contrast to the Ala204Glu mutation which has been implicated in short stature with dominant transmission; recessive GHS-R mutations have also been reported (Pantel et al, 2009). The proband was born to unrelated parents of normal phenotype, presented with episodes of abdominal pain, vomiting, hypoglycemia, and ketosis and required glucose infusions.…”
Section: Ghs-r Mutations In Patientsmentioning
confidence: 97%
“…GHS-R sequencing revealed that the patient was compound heterozygous for two new defects: a mutation predicting a premature stop codon (Trp2X) inherited from his unaffected father, therefore strongly arguing against haploinsufficiency as a disease mechanism, and a missense mutation (Arg237Trp), inherited from his healthy mother (Pantel et al, 2009).…”
Section: Ghs-r Mutations In Patientsmentioning
confidence: 99%
“…Later, this group also reported a patient with isolated GH deficiency due to compound heterozygous GHSR mutations (10). Similarly, a significantly higher occurrence of four novel heterozygous GHSR variants was observed in 127 Japanese patients with either GH deficiency or short stature compared with controls (4.72 vs 0.53%) (11).…”
Section: Introductionmentioning
confidence: 91%
“…We used two naturally occurring GHSR mutations that lead to either partial or complete lack of basal ligand-independent activity: A204E and F279L (supplemental Fig. S2) (36,37). Such mutations can be termed silencing mutations, inverse agonistic mutations, or constitutively inactivating mutations.…”
Section: Coexpression Of Mc3r and Ghsr In Hypothalamic Neurons-mentioning
confidence: 99%